2020
DOI: 10.24191/myse.v7i2.10269
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Distribution of Microplastics in Surface Sediment of Selat Pulau Tuba, Langkawi, Kedah

Abstract: This study aims to assess the characteristics and occurrence of the microplastics contamination in surface sediment of Selat Pulau Tuba, Langkawi, Kedah. Van Veen Grab Sampler was used to collect the samples of sediment. The samples were immediately preserved and analyzed using a Fourier-transform infrared spectrophotometer and a microscope to determine the presence and characteristics of microplastics. The result indicates the presents of polypropylene and polyethylene with a size of 500 µm -1000 µm and 1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Overall, spline has been known to be generating gently varying surfaces such as pollution concentrations [18]. GIS has been proven to be effective tools and software for visualizing and presenting the variation of water pollutants in a study area [19].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, spline has been known to be generating gently varying surfaces such as pollution concentrations [18]. GIS has been proven to be effective tools and software for visualizing and presenting the variation of water pollutants in a study area [19].…”
Section: Resultsmentioning
confidence: 99%
“…The island has many biodiversity species that flourish from the coastal, marine, and mangrove ecosystems. The socio-economic activities by the locals are farming, fishing and operating tourism activities (Kamaruddin et al, 2020b). Pollution can be expected from non-point sources from Pulau Langkawi, however, point source pollution directly from the islands is considered minimal (Kamaruddin et al, 2019).…”
Section: Methodology Description Of Study Areamentioning
confidence: 99%
“…Water quality, including hydrology, is a significant component of river health evaluations because it affects the spatial and temporal dynamics of various biological patterns and processes in major rivers (Kamaruddin et al, 2022;Mohd Rizal et al, 2022;Sheldon & Fellows, 2010). Studies have found that surface waters are the most polluted due to their easy availability for wastewater dumping (Kamaruddin et al, 2020;Samsudin et al, 2011). Malaysia's latest river water quality was examined in 2020 using 8,098 samples from 1,353 manual monitoring stations covering 672 rivers.…”
Section: Introductionmentioning
confidence: 99%
“…The total solid content in water bodies has adverse and detrimental effects on health and the ecosystem. Solids can degrade the quality of water or wastewater in various ways, and controlling biological and physical wastewater treatment processes requires solids analyses (Al-Badaii et al, 2013;Kamaruddin et al, 2020). Total solids include "total suspended solids," which a filter retains, and "total dissolved solids," which go through the filter (American Public Health Association, 1999).…”
Section: Introductionmentioning
confidence: 99%